Penggunaan Media PowerPoint untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar Mata Pelajaran Pendidikan Agama Islam Materi Bersuci - Budi Hata (Jurnal Indonesia Pendidikan Profesi Guru, 2024)
One aspect that needs to be considered in the learning process is fostering student learning motivation and this is important for teachers to do. Motivation is one of the factors that determine student learning outcomes. The purpose of this study was to determine how much influence the use of PowerPoint media has to increase learning motivation in Islamic religious education subjects on the material of washing in students of SD Negeri 87 Bengkulu Tengah. The research method uses Classroom Action Research. The research location was carried out at SD Negeri 87 Pondok Kubang District, Central Bengkulu Regency. The research sample is class IV students totaling 18 students. Data collection techniques researchers use (1) observation; (2) worksheets and reflection; and (3) tests. In the data analysis process using the completeness of learning outcomes. The results revealed that the conclusion of the study revealed that learning using PowerPoint media with pictures combined with videos can attract students' attention to participate in learning. The pictures and videos shown in the slides are very interesting for students and provoke students to play an active role in learning, for example commenting on the picture.